KONSTITUSIONALITAS PRESIDENTIAL CANDIDACY THRESHOLD DALAM PEMILIHAN UMUM SERENTAK - Jamil Jamil; Sofie Rahma Dewi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
Political party coalition is an inevitability during the multi-political party presidential administration in general election mechanism of president and vice-president election. Coalition formed in general election sphere, as stated in Law Number 7 Year 2017 regarding of General Election to fulfil the minimum 20% quota as general election participant and win the general election and coalition in the politic sphere to fill up the ministerial position. Incumbent presence as a pair of candidates implied to coalition chartering by the incumbent candidate that causes the contest not to be able to be followed by more than two pairs of candidates. It is the contrary to article 6a clause (3) and (4) of Indonesia Constitution 1945 that require the candidate to be appointed as president and vice president if they receive more than 50% of votes with the spread of 20% of votes in each province which consist of more than half of Indonesia’s total province, if not fulfilled then second round should be done, followed by two pairs of candidates that receives the highest votes. That means, constitution design was not only followed by two pairs of candidates. The implementation of presidential candidacy threshold in general election law and incumbent candidate closes the design. This research analyzes the presidential candidacy threshold constitutionality in simultaneous general election by using statute and conceptual approach.